2021
DOI: 10.1155/2021/1807293
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Replication of Human Parainfluenza Virus Type 3 by Affecting Viral Inclusion Body Formation

Abstract: Human Parainfluenza Virus Type 3 (HPIV3) is one of the main pathogens that cause acute lower respiratory tract infections in infants and young children. However, there are currently no effective antiviral drugs and vaccines. Herein, we found that a natural compound, curcumin, inhibits HPIV3 infection and has antiviral effects on entry and replication of the virus life cycle. Immunofluorescence and western blotting experiments revealed that curcumin disrupts F-actin and inhibits viral inclusion body (IB) format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The balance between NRF2 activation and the interferon response is regulated by intrinsic cell factors, for which the cell composition varies from nasal to bronchial cells, and potentially influences the susceptibility to viral infections. Notably, activation of the NRF2 pathway appears to mediate protection against viral respiratory infections, including SARS-CoV-2, influenza viruses, and several RNA and DNA viruses that induce oxidative stress (Supplementary Table S1) [5,[8][9][10][11][12][13][14][18][19][20][21][22][23][24][27][28][29][30][31][32][33][34][35][36][41][42][43][44][46][47][48][49][51][52][53][54]. Overall, the crosstalk between NRF2 and viruses is bidirectional and complex.…”
Section: The Nrf2 Pathway Regulates Cellular Responses To Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The balance between NRF2 activation and the interferon response is regulated by intrinsic cell factors, for which the cell composition varies from nasal to bronchial cells, and potentially influences the susceptibility to viral infections. Notably, activation of the NRF2 pathway appears to mediate protection against viral respiratory infections, including SARS-CoV-2, influenza viruses, and several RNA and DNA viruses that induce oxidative stress (Supplementary Table S1) [5,[8][9][10][11][12][13][14][18][19][20][21][22][23][24][27][28][29][30][31][32][33][34][35][36][41][42][43][44][46][47][48][49][51][52][53][54]. Overall, the crosstalk between NRF2 and viruses is bidirectional and complex.…”
Section: The Nrf2 Pathway Regulates Cellular Responses To Stressmentioning
confidence: 99%
“…With regards to the impact of viruses on the NRF2 pathway, respiratory viruses such as influenza [12,94], SARS-CoV-2 [19,20,22,24,95,96], RSV [27,31,32], rhinovirus [43,44], and enteroviruses [47] directly alter NRF2 levels and signaling [5,[8][9][10]18,33] (Table 1). With regards to the impact Pathogens 2024, 13, 39 3 of 24 of the NRF2 pathway on viruses, host NRF2 pathways also regulate the replication of several respiratory viruses such as influenza [11][12][13], coronaviruses [19][20][21][22][23], RSV [34,35], rhinovirus [44], enterovirus [47], metapneumovirus [34], and parainfluenza [51,52] (Table 2). Notably, the host NRF2 pathways also regulate viral replication, apoptosis, ferroptosis, and inflammation (Tables 2-6).…”
Section: The Nrf2 Pathway Regulates Cellular Responses To Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-HPIV3 activity of curcumin was evaluated by one study. This study showed that curcumin disrupts F-actin, resulting in reduced viral inclusion body (IB) formation and inhibiting virus replication [58].…”
Section: Human Parainfluenza Virus Typementioning
confidence: 99%
“…Viruses cause 30%–70% of ARI, with respiratory syncytial virus (RSV) and parainfluenza virus (PIV) accounting for the majority of these cases ( Hatem et al, 2019 ). PIV is a common acute viral respiratory infection, primarily causing lower respiratory tract infections in infants and young children ( Maeda et al, 2017 ; Zhang et al, 2021 ). In adults, it mainly manifests as an upper respiratory tract infections ( Essa et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%